Alexander Polynomial Invariants of Torus Knots T(n, 3) and Chebyshev Polynomials - Gavrilik, A.M.; Pavlyuk, A.M. (Ukrainian Journal of Physics, 2022)
The explicit formula, which expresses the Alexander polynomials ∆n,3(t) of torus knots T(n, 3) as a sum of the Alexander polynomials ∆k,2(t) of torus knots T(k, 2), is found. Using this result and those from our previous papers, we express the Alexander polynomials ∆n,3(t) through Chebyshev polynomials. The latter result is extended to general torus knots T(n, l) with n and l coprime.